Academic Aspect of the Leather Industry: An Interpretation from the Perspective of Business Science - Hatice ER (Prizren Social Science Journal, 2021)
In the leather industry, a production process that is the subject of many different disciplines is dominant. Many studies on these branches of science have examined the sector in detail in terms of production. On the other hand, studies dealing with the sector in terms of business administration department and sub-disciplines are not common.